Fine-tuning electroconvulsive therapy: A cognitive comparison of brief and ultra-brief pulse widths - Vishesh Yadav,; Abhishek Pathak,; Rahul Singh,; Jaymin Maganbhai Pandav,; Divya Kushwaha,; Manish Singh,; Yogi Rana, (Asian Journal of Medical Sciences, 2025)
Background: Electroconvulsive therapy (ECT) has been a cornerstone in managing severe psychiatric illnesses. However, concerns about its cognitive side effects have led to evolving techniques aimed at minimizing cognitive impairments. Specifically, the use of ultra-brief pulse width (0.5 ms) compared to brief pulse width (1.5 ms) in bitemporal modified ECT (MECT) offers a promising avenue for cognitive preservation.Aims and Objectives: To compare the cognitive outcomes associated with brief and ultra-brief pulse widths in bitemporal MECT.Materials and Methods: This prospective, randomized comparative study was conducted at a rural tertiary care hospital in Northern India. Sixty-six patients aged 18–60 years, diagnosed with schizophrenia, schizoaffective disorder, bipolar disorder, or severe depression, were randomly assigned to receive either brief or ultra-brief pulse MECT. Cognitive functions were assessed using standardized tools, including the Hindi mental status examination and Battery for ECT-related cognitive deficits. Pre- and post-treatment evaluations were compared to determine changes in cognitive performance.Results: Both groups exhibited some level of cognitive change following treatment. However, patients receiving ultra-brief pulse MECT demonstrated significantly better preservation of cognitive functions, notably in memory retention, attention, and executive functioning (P